Akumulasi Beban Berganda Zakat dan Pajak dalam Perspektif Hukum Islam - Sri Wahyuni (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2020)
This study aims to determine the perspective of Islamic law on the double burden accumulation of zakat and tax. This study use a qualitative aaproach with the type of library research and use the content-descriptive analysis. This research founds many fundamental differences between zakat and tax, so that the unification of zakat and tax according Islamic law is based on the quran and hadith as well as the ijtihad of the thought of scholars, the accumulation of zakat and tax is irrelevant. Some suggestions have implication that there is a need for profesional zakat management which is directly handled by to govemment. By establishing a zakat institution which is equal to the director general of taxation accompanied by laws as with the establishment of trax institution, so as maximize zakat income which will be used to improve the standard of living of the community.